2023
DOI: 10.1021/acs.jpcb.2c07997
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Force Fields for the Prediction of Thermophysical Properties of Long Linear and Branched Alkanes

Abstract: The prediction of thermophysical properties at extreme conditions is an important application of molecular simulations. The quality of these predictions primarily depends on the quality of the employed force field. In this work, a systematic comparison of classical transferable force fields for the prediction of different thermophysical properties of alkanes at extreme conditions, as they are encountered in tribological applications, was carried out using molecular dynamics simulations. Nine transferable force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 113 publications
1
24
1
Order By: Relevance
“…Unsurprisingly, a large number of molecular dynamics (MD) force fields for alkanes are available with a wide range of potential energy functions and levels of coarse graining, as well as lipid force fields which can be readily adapted. Their performance has been reviewed for reproducing different alkane properties such as liquid phase transport , or phase transition temperatures and solid phase ordering. , Here, we focus on studies looking specifically at modeling of rotator phases for higher alkanes.…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly, a large number of molecular dynamics (MD) force fields for alkanes are available with a wide range of potential energy functions and levels of coarse graining, as well as lipid force fields which can be readily adapted. Their performance has been reviewed for reproducing different alkane properties such as liquid phase transport , or phase transition temperatures and solid phase ordering. , Here, we focus on studies looking specifically at modeling of rotator phases for higher alkanes.…”
Section: Introductionmentioning
confidence: 99%
“…The density of hexadecane calculated by this forcefield under 500 MPa is 890 kg/cm 3 , as shown in ref , which corresponds to the bulk density for n -hexadecane under the same load, according to the Dowson–Higginson equation for the bulk compressibility of liquids . A more accurate version for OPLS forcefield is the L-OPLS force field, which is an optimized version for long linear alkanes and shows significantly better results for predicting thermophysical properties of long linear and branched alkanes than other forcefields . Compared to LOPLS-AA forcefield, OPLS-UA reduces the number of atoms in the system; meanwhile, the computation cost of the C–H bond’s vibration and coulomb interaction is also decreased.…”
Section: Methodsmentioning
confidence: 99%
“…31 A more accurate version for OPLS forcefield is the L-OPLS force field, 32 which is an optimized version for long linear alkanes and shows significantly better results for predicting thermophysical properties of long linear and branched alkanes than other forcefields. 33 Compared to LOPLS-AA forcefield, OPLS-UA reduces the number of atoms in the system; meanwhile, the computation cost of the C−H bond's vibration and coulomb interaction is also decreased. Harmonic bonds impose restrictions on the atoms in hematite slabs; bonding only happens when the distance between atoms is less than 3 Å.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Assessments have shown that all-atom and united-atom models could provide improved accuracy in representing thermodynamic properties over the CG models, as noted in recent benchmark studies. 75,76…”
Section: Methodsmentioning
confidence: 99%
“…Assessments have shown that all-atom and united-atom models could provide improved accuracy in representing thermodynamic properties over the CG models, as noted in recent benchmark studies. 75,76 Fig. 1 demonstrates equilibrium snapshots of the molecular system for studying the interfacial properties of the H 2 + H 2 O + decane three-phase mixture.…”
Section: Molecular Simulationmentioning
confidence: 99%